Effect of Vaccinium bracteatum Thunb. leaf pigment on the thermal, pasting, and textural properties and microstructure characterization of rice starch. (1st August 2017) - Xu, Yuan; Fan, Mingcong; Zhou, Sumei; Wang, Li; Qian, Haifeng; Zhang, Hui; Qi, Xiguang
Highlights: The interaction between VBTLP and two types of rice starch was investigated. VBTLP reduces the gelatinization and retrogradation enthalpy of two rice starches. VBTLP significantly affects the pasting properties of the two types of starch gel. VBTLP can cause a looser gel matrix in both types of starch gel. Hydrogen and hydrophobic bonds play a major role in these interactions. Abstract: In this study, the thermal, pasting and gel textural properties of japonica rice starch (JRS) and glutinous rice starch (GRS) fortified with Vaccinium bracteatum Thunb. leaf pigment (VBTLP) were investigated. The results showed that VBTLP facilitated the gelatinization of JRS and GRS with earlier onsets of onset temperature (To ), peak temperature (Tp ), conclusion temperature (Tc ), and lower values of gelatinization enthalpy (ΔHg ), and retrogradation enthalpy (ΔHr ), as the VBTLP level increased. For JRS, VBTLP increased the peak viscosity and breakdown, reduced the final viscosity and setback, but for GRS it increased the peak viscosity, final viscosity, breakdown and setback. VBTLP also reduced the hardness and adhesiveness of the JRS gel. The values of lightness (L ∗ ) for JRS and GRS with VBTLP decreased by 47.60 and 49.56%, respectively. Scanning electron microscopy (SEM) revealed that VBTLP caused looser matrices in dried JRS and GRS gels which had lower crystallinities compared with the control.